Saussurea lappa: An Important Medicinal Plant for Treatment Different Diseases: A review - Alaq Ali; Kawther Alqaseer; Duaa Fatlawi; Salma Shehab; Mansour Falah; Mohammed Hassan; Wijdan Shnain; Ohoud Radhi (Kufa Journal for Nursing Sciences)
Saussurea lappa is belong to the family Astreaceae. It has been cultivated in various parts of the world a commonly known and potent plant which is well studied for its medicinal uses in diverse indigenous Indian systems of medicine. It is usually known as kuth root or costus and used in different system of medicine to treat various diseases such as asthma, ulcers and stomach problems. Indian medical systems use various preparations prepared from the roots by physicians to treat cough, cold, stomachache, toothache, typhoid and fever. It is an important drug for gout and erythroderma and stimulates spermatogenesis. Several of its activities are proved and confirmed through in viro and in vivo approaches which gave a rational scientific way to the traditional claims. As a result to the significant proven activities Saussrea lappa is having major chance for new drug discovery.